Evaluation of a new whole room indirect calorimeter specific for measurement of resting metabolic rate. Issue 1 (December 2015) - Rising, Russell; Whyte, Kathryn; Albu, Jeanine; Pi-Sunyer, Xavier
Abstract Background The most common methods for obtaining human resting metabolic rate (RMR) use either a ventilated hood connected to a metabolic cart (VH_MC) or calculation by many prediction equations utilizing the person's height and weight. These methods may be inherently inaccurate. The objective of this study is to compare the accuracy for the measurement of RMR by three methods: a new whole room indirect calorimeter specific for this purpose (RMR_WRIC), VH_MC and calculation by the Mifflin equation (ME). First, the VH_MC (Vmax Encore 2900, Carefusion Inc, San Diego, CA) and RMR_WRIC (Promethion GA-6/FG-1, Sable Systems Intl, Las Vegas, NV) were subjected to 10, one-hour ethanol (99.8 % purity) and propane (99.5 % purity) combustion tests, respectively, for simulated metabolic measurements. Thereafter, 40 healthy adults (22 M/18 F, 78.0 ± 24.5 kg, BMI = 25.6 ± 4.8, age 36.6 ± 13.4 years) had one-hour RMR (kcal), ventilation (liters) rates of oxygen (VO2 ), carbon dioxide (VCO2 ) and RQ (VCO2 /VO2 ) measured after a 12-h fast with both the VH_ MC and the RMR_WRIC in a randomized fashion. The resting state was documented by heart rate. The RMR was also calculated using the ME, which was compared to both the RMR_WRIC and the VH_MC. All simulated and human metabolic data were extrapolated to 24-h and analyzed (SPSS, Ver. 22). Results Comparing stoichiometry to actual combustion, the VH_MC underestimated simulated RMR (p  < 0.05), VO2 (p  < 0.05), VCO2 (p  < 0.05) and the RQ. Similarly the RMR_WRIC underestimated simulated RMR (p  < 0.05) and VO2 while overestimating VCO2 and the RQ. There was much greater variability in the simulated metabolic data between combustion and the VH_MC as compared to that of the RMR_WRIC. With regards to the volunteers, the RMR, RQ, VO2 and VCO2 determined by the VH_MC tended to be lower in comparison to these measurements determined by the RMR_WRIC. Finally, RMR calculated utilizing the ME was significantly (p  < 0.05) less than the RMR_WRIC but similar to that obtained by the VH_MC. Conclusion The RMR_WRIC was more accurate and precise than either the VH_MC or ME, which has implications for determining energy requirements for individuals participating in weight loss or nutrition rehabilitation programs.